2020
DOI: 10.1101/lm.050211.119
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a reminder/extinction procedure on threat-conditioned pupil size and skin conductance responses

Abstract: A reminder can render consolidated memory labile and susceptible to amnesic agents during a reconsolidation window. For the case of threat memory (also termed fear memory), it has been suggested that extinction training during this reconsolidation window has the same disruptive impact. This procedure could provide a powerful therapeutic principle for treatment of unwanted aversive memories. However, human research yielded contradictory results. Notably, all published positive replications quantified threat mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 56 publications
3
7
0
Order By: Relevance
“… 103 105 ). We suggest that our findings are in line with the literature that is unable to replicate the reminder-extinction effects on conditioned threat memories in humans 36 , 55 , 56 , 58 62 , 71 , where we note that ours diverges specifically in that we investigated contextual threat memories using iVR. The limited replicability may not be limited the reminder-extinction procedure, but could generalize to reconsolidation-based interventions 106 , 107 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“… 103 105 ). We suggest that our findings are in line with the literature that is unable to replicate the reminder-extinction effects on conditioned threat memories in humans 36 , 55 , 56 , 58 62 , 71 , where we note that ours diverges specifically in that we investigated contextual threat memories using iVR. The limited replicability may not be limited the reminder-extinction procedure, but could generalize to reconsolidation-based interventions 106 , 107 .…”
Section: Discussionsupporting
confidence: 89%
“…We followed our preregistered design and analyses with a few minor exceptions, which we clearly indicate below. In contrast to our hypotheses, yet in line with previous non-replications for cue conditioned threat memories 55 , 56 , 58 61 , 71 73 , contextual conditioned threat memories 71 and category threat conditioned memories 36 , we found comparable recovery of context conditioned threat responses in the extinction group and the reminder-extinction group, and no group differences on either avoidance behaviour or the other memory tests, suggesting that the reminder-extinction procedure did not modify contextual threat memories in humans.
Figure 1 Three-day between-subjects iVR contextual threat conditioning study design.
…”
Section: Introductionsupporting
confidence: 77%
“…This experimental paradigm and its variants have been reported to extinguish fear- and addiction-related memory in humans (Bjorkstrand et al, 2016 ; Agren et al, 2017 ; Lee et al, 2017 ; Thompson and Lipp, 2017 ; Chen et al, 2019 ; Kitamura et al, 2020 ). However, reproducibility issues in the field (Kredlow et al, 2018 ; Zimmermann and Bach, 2020 ) have suggested that this effect is sensitive to procedural differences. A meta-analysis established that retrieval extinction had a negligible to moderate influence on impeding recovery of the fear responses compared with standard extinction (Kredlow et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…B.14. 2020 Zimmermann and Bach [80]: "Impact of a reminder/extinction procedure on threatconditioned pupil size and skin conductance responses" Once again, replicating experiment 2 of Schiller et al [7] was the purpose of this study, but with SCR measurement supplemented by measurement of another autonomic response, pupil size response (PSR). The authors note that (p. 165) "a direct comparison has revealed that PSR may have higher accuracy in inferring fear memory than SCR (Korn et al 2017)."…”
Section: B11 2018 Zuccolo and Hunzigermentioning
confidence: 99%
“…These researchers also (p. 165) "optimized some parameters in light of a recent meta-analysis by Kredlow et al (2016), in order to increase the chances of revealing success of the reminder/extinction procedure…." The parameters used by Zimmermann and Bach [80] and [Schiller et al [7]] are listed here: In addition to those optimizations, this study's statistical power was slightly stronger than that of Schiller et al [7]: "Our sample size was based on the signal-to-noise ratio of PSR under control conditions. Thus, we recruited a sample that provided 85% power to detect an at least 50% absolute reduction of fear retention, corresponding to the ∼60% reduction found in Schiller et al ( 2010)" (p. 165).…”
Section: B11 2018 Zuccolo and Hunzigermentioning
confidence: 99%